Ultramorphology and histology of the ectal mandibular gland in Polistes versicolor (Olivier) (Hymenoptera: Vespidae) - Ortega Pietrobon, Thiago Augusto (2003)
The ectal mandibular gland (EMG) of wasps is homologous to the mandibular gland of ants and bees. This gland belongs to salivary system and its function stile unknown. The EMG of Polistes versicolor showed histological and ultramorphological features similar to that founded in ants and others wasps. This gland is constituted by a secretory region and a reservoir. The secretory region contains individual secretory cells that showed several nucleoli. The reservoir has a club shape and is connected to each mandible, by a duct that opens on its external side, which there are cuticular projections. The EMG of males is smaller than those of females. Our results suggested that the EMG secrete volatiles compounds that are liberated when the mandibles still open.